Sarbanes Oxley Act: The Unintended Consequences and Financial Restatements - Wokukwu, Kingsley (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
The present study aimed to compensate for the failure of governances that culminated in Enron, WorldCom and Tyco financial scandals. Corporate managers are being held accountable for corporate governance and Sarbanes Oxley Act also detects what firms can and cannot do. This paper argues that Sarbanes Oxley Act has given investors a fresh breath of life with a renewed sense of confidence in the US financial market. Sarbanes Oxley Act tend to minimize corporate collapses, audit failures and litany of financial restatements that permeated the corporate arena, the financial market several years and bred deep cynicism and public anger. The new standard would require the auditor’s opinion to refer to the Board’s authority. Prior to Sarbanes Oxley Act; auditors were governed by a system of self regulation which did not preserve their ability to act independently and objectively to be watchdogs. The Sarbanes-Oxley Act is signed into law in order to restore investor confidence in public and financial markets through a combination of rules and oversight that address conflict of interest on the investor side and a lack of accountability on the corporate side in order to improve corporate governance. Firms have better internal control environment as a result of Sarbanes Oxley Act. This translates to a more accurate and reliable information conveyed to investors who would rely on published financial statements to make informed investments decisions.